Dasar-dasar kesefahaman Malaysia dan Indonesia berkaitan tenaga kerja (Policies related labour between Malaysia and Indonesia) - Azed, Abdul Bari (2013)
Migration is movement of human from the area of origin to another destination. A migration decision based on comparison of profit and loss related to the purpose of the district. Migration process occurs is to improve the lives of migrants and their families, so they are generally able to find jobs that provide higher income and social status.International migration occurs when people cross state boundaries of a country to another country. Generally, a person migrates abroad to obtain better financial status to himself and family.Malaysia and Indonesia have held an agreement on supplying workers and aims to strengthen the diplomatic relationship established between Malaysia and Indonesia. Both countries intend to further the relationship and help each other in improving the economic and technical cooperation, especially in the provision of manpower. Protection of the basic rights of Indonesian workers in Malaysia was established by the government.A form of protection that had previously been agreed upon by Malaysia and Indonesia is through a Memorandum of Understanding (MoU) on formal Indonesian workforce and informal workforce.